Ética e persuasão no contexto humano-máquina: uma reflexão sobre a algoritmização das relações sociais na cibercultura - Soares, Maytê de Carvalho (2023)
This research aims to investigate how the consumption of information through digital platforms is linked to the algorithmization of social relations, incorporating behaviors and subjectivities through digital information and communication technologies that manifest in cyberculture. The objective is to examine the impacts on persuasive practices in the face of this new hierarchy of information circulation. It delves into the surveillance theories of the Anglo-Saxon tradition of Lyon and Zuboff to understand the ethical boundaries between publishers and platforms in editorial control of content and the algorithmization of relationships. The methodology is based on qualitative documentary research. The hypothesis asserts that, under Capitalism and the Surveillance Culture, platforms show no ethical concern and do not assume editorial responsibility regarding content moderation and distribution